Special Collections as Information Policy for Culture of Indonesia - Grataridarga, N (KnE Social Sciences, 2018)
This research discusses the information policy in Indonesia. It aims to identify and apply information policy as a general term for all legal, regulatory, and doctrinal positions relating to information, communication, and culture. The information policy in line with government regulations on public library to develop cultural peculiarities of each region into a center for research and reference. This research used a qualitative method by observation and interview with descriptive analysis. The results showed that the Jakarta public library and Riau public library (Soeman H.S. library) already have special collections of the regional culture. The implementation of the information policy through a special collection that is owned by the Jakarta and Riau public library has a great potential as a center for information, research, preservation, even tourism with good management and a massive promotion. Keywords: information policy, special collections, Jakarta public library, Riau public library